If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x-6)(-8x+1)=0
We multiply parentheses ..
(-56x^2+7x+48x-6)=0
We get rid of parentheses
-56x^2+7x+48x-6=0
We add all the numbers together, and all the variables
-56x^2+55x-6=0
a = -56; b = 55; c = -6;
Δ = b2-4ac
Δ = 552-4·(-56)·(-6)
Δ = 1681
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{1681}=41x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(55)-41}{2*-56}=\frac{-96}{-112} =6/7x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(55)+41}{2*-56}=\frac{-14}{-112} =1/8
| 3x-40=x/2+20 | | 7x+20=5x-9 | | 0=1.5x^2+4x | | Y=7/6x+6 | | 6x-1-(3x-3)=3 | | 2700=6800x | | 8x^2=500 | | 7x+31=10 | | 40÷3q=15 | | 3(x+5)/4+-7(x+3)/10=4 | | 3x/8-3=-5 | | 3*x+x/5-5=1/5+5*x | | 5/8t+14=-1 | | 4q+20=16 | | 12(t+4)-8=88 | | 1/5x+1/3=-1 | | 8c-6=15 | | 2x-8=130 | | x-5/3+4x-9/12=5x-32/9-x+9/21 | | 2(3x+5)=x^2 | | 5t-3=2t+4 | | 186=x-x(.07) | | 2x2-6=3x | | 7x-35=70 | | -6(1-7n=36 | | 10x+7=-14+x | | -6(7x+8)=36 | | -6(-7n-8=-8 | | (x+5)^2+9(x+5)+14=0 | | 80+5x=90 | | P=300+2x | | 6=3-n |